Phonological Awareness in Specific Learning Disability: A Journey into Search for Genetic Inheritance - Deepa M.S.; Prema K.S. (Journal of All India Institute of Speech and Hearing, 1970)
Specific learning disability (SLD) is a condition debated for long particularly for the causation. The genetic nature of specific learning disability in particular, has been widely discussed. The recent literature increasingly highlights the associated phonological skill deficits as the underlying core cause for the genetic inheritance with SLD. The present study aimed at comparing the phonological skills of families of children with SLD with that of children and adults without SLD. Three families of children with first cousins, the siblings and only one child in family who were diagnosed as having SLD were selected for the study along with the normal sibling and both the parents. All were tested on phonological tasks. Results were compared with normal children and normal adults. The results indicate that both the qualitative and quantitative performance of children with learning disability matched with that of their fathers suggesting a possibility of tracing genetic inheritance with behavioral measures such as phonological awareness skills. The study opens-up a possibility of devising low cost and non-invasive protocol to explore genetics as a causative factor by clinician that would facilitate better counseling and prognosis. An investigation of performance of children with SLD and their family on phonological tasks revealed a possibility of underlying phonological skill deficits as the cause for SLD, than the inheritance of specific learning disability per se.